A 2 °C warmer world is not safe for ecosystem services in the European Alps. (13th March 2013) - Elkin, Ché; Gutiérrez, Alvaro G.; Leuzinger, Sebastian; Manusch, Corina; Temperli, Christian; Rasche, Livia; Bugmann, Harald
Abstract: Limiting the increase in global average temperature to 2 °C is the objective of international efforts aimed at avoiding dangerous climate impacts. However, the regional response of terrestrial ecosystems and the services that they provide under such a scenario are largely unknown. We focus on mountain forests in the European Alps and evaluate how a range of ecosystem services (ES) are projected to be impacted in a 2 °C warmer world, using four novel regional climate scenarios. We employ three complementary forest models to assess a wide range of ES in two climatically contrasting case study regions. Within each climate scenario we evaluate if and when ES will deviate beyond status quo boundaries that are based on current system variability. Our results suggest that the sensitivity of mountain forest ES to a 2 °C warmer world depends heavily on the current climatic conditions of a region, the strong elevation gradients within a region, and the specific ES in question. Our simulations project that large negative impacts will occur at low and intermediate elevations in initially warm‐dry regions, where relatively small climatic shifts result in negative drought‐related impacts on forest ES. In contrast, at higher elevations, and in regions that are initially cool‐wet, forest ES will be comparatively resistant to a 2 °C warmer world. We also found considerable variation in the vulnerability of forest ES to climate change, with some services such as protection against rockfall and avalanches being sensitive to 2 °C global climate change, but other services such as carbon storage being reasonably resistant. Although our results indicate a heterogeneous response of mountain forest ES to climate change, the projected substantial reduction of some forest ES in dry regions suggests that a 2 °C increase in global mean temperature cannot be seen as a universally 'safe' boundary for the maintenance of mountain forest ES.